Clonal propagation through improved stem cutting technique in Pongamia pinnata (L.) Pierre - Kala, S.; Kumaran, K.; Uthappa, A.R.; Reeja, S.; Prabhavathi, M.; Rashmi, I.; Singh, R.K. (Indian Journal of Agroforestry, 2020)
Present study describes the scope of macroclonal propagation of Pongamia pinnata through stem cutting which is indigenous and important nitrogen-fixing tree species, suitable for dryland agroforestry system and degraded land rehabilitation. Improved method of clonal propagation for this multipurpose tree is needed for agroforestry or biofuel park development. This study was conducted to standardize the propagation techniques with focus on the effects of stem cutting size, rooting media and concentration of IBA. The results revealed that percentage rooting and primary root number differed significantly between treated and untreated cuttings. The 15 cm length Ã— 25 mm diameter (medium) cuttings, when dipped in IBA of 3000 ppm solution for five minutes and planted in sand : soil: VAM (2:1:1), yielded best results in terms of root initiation, number of roots per cutting, root length and survival percentage of stem cuttings of P. pinnata.